2007
DOI: 10.1007/s11126-006-9035-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Darryl, a Cartoon Based Measure to Assess Community Violence-Related PTSD in Children

Abstract: In comparison to other child PTSD measures, Darryl has comparable or better psychometric properties and assesses PTSD symptoms in a more developmentally appropriate manner, especially in the domain of community violence. The value of Darryl as a screening tool remains preliminary given the limited number of diagnosed cases of PTSD in the study sample. Full scale efforts at replication are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The screening tool has demonstrated good internal consistency for PTSD symptomology as detailed in the DSM-IV. Studies have shown that Darryl assesses PTSD symptoms in a developmentally appropriate manner [30]. The test is designed to be used on children between the ages of 5 and 18.…”
Section: Methodsmentioning
confidence: 99%
“…The screening tool has demonstrated good internal consistency for PTSD symptomology as detailed in the DSM-IV. Studies have shown that Darryl assesses PTSD symptoms in a developmentally appropriate manner [30]. The test is designed to be used on children between the ages of 5 and 18.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with previous studies of American children (Geller et al , ; Neugebauer et al , ), the Darryl exhibited good internal consistency for the full scale and adequate reliability for the symptom subscales in this sample of Danish children and adolescents. Furthermore, this study found support for the construct and criterion validity of Darryl.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of avoidance for children and adolescents include a sense of foreshortened future, where they believe they will not live long enough to become adults (Terr, ). Verbalizing and detecting avoidance symptoms can be difficult especially for younger children (Geller et al , ) and often information is needed from teachers or parents to establish the presence of these symptoms. Hyperarousal symptoms for children and adolescents include insomnia, irritability, and difficulties in concentrating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Darryl's cartoon test is a screening tool used to identify and measure PTSD symptoms in children and adolescents [44,50]. The test consists of 23 cartoons of a pre-adolescent boy named Darryl, accompanied by three empty, half-full, and full thermometers.…”
Section: Child Psychopathologymentioning
confidence: 99%